The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jpbm-09-2018-2017
|View full text |Cite
|
Sign up to set email alerts
|

The role of private label tiers and private label naming strategies in the relationship between private label brand equity and store loyalty

Abstract: Purpose The evolution of private labels (PL) is a recent trend in the retail industry: many retailers now manage a PL portfolio that includes multiple value propositions, as well as various brand name strategies. Little research has been done, however, on how this combination of PL strategies conditions the results of the retailer that manages them. This study aims to examine the formation of PL brand equity and its effect on store loyalty for retailers with differently tiered PL programs (a “better” program w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 64 publications
1
16
0
1
Order By: Relevance
“…Hypothesis 7 is therefore partially supported by our data. Thus, this research partially confirms previous studies (Martos-Partal and González-Benito, 2011; Diallo et al , 2015; Rubio et al , 2019) that indicated that SBs' positioning has an impact on consumers' behaviour (e.g. their loyalty to the SBs/the store or the value of the store).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Hypothesis 7 is therefore partially supported by our data. Thus, this research partially confirms previous studies (Martos-Partal and González-Benito, 2011; Diallo et al , 2015; Rubio et al , 2019) that indicated that SBs' positioning has an impact on consumers' behaviour (e.g. their loyalty to the SBs/the store or the value of the store).…”
Section: Resultssupporting
confidence: 89%
“…copycat) has a more favourable effect on store loyalty than positioning that prioritizes price over quality (generic SBs). Recently, Rubio et al (2019) indicated that in portfolios with economy, standard and premium SBs, SB associations have a stronger effect than SB awareness in the formation of SB loyalty. Portfolios with a standard SB show balanced effects of SB associations and SB awareness on SB loyalty formation.…”
Section: Theoretical Framework and Research Hypothesesmentioning
confidence: 99%
“…As previously stated, OBE always shows a positive and significant influence on other consumer behavior construct(s), such as store loyalty (Rubio et al, 2019), advocacy behavior (Baghi et al, 2016), and surely purchase intention (Chen and Chang, 2008;Moradi and Zarei, 2011;Tharmi and Senthilnathan, 2012;Buil et al, 2013;Shah et al, 2016;Vahdati and Nejad, 2016;Samadi et al, 2017;Akturan, 2018;Poturak and Softic, 2019). However, among MBE based studies, there are conflicting results.…”
Section: Brand and Brand Equity In Higher Educationmentioning
confidence: 94%
“…International and national brands refer to those which are found in many countries around the world, while regional brands refer to those generally available in one country or a narrow geographical area (Winit et al, 2014). OBs have a variety of price and branding strategies which appeal to different consumer segments, with tiered product portfolios often used, rather than a single standard OB range (Lessassy, 2019;Rubio et al, 2019). Value ranges follow an economy strategy, avoiding expensive ingredients and packaging (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%